(untitled) (Window of Public Health Journal, 2026)
Bottled Drinking Water (AMDK) is a widely consumed drinking water source because it is practical and considered hygienic. However, various studies have shown that bottled water can be contaminated with microplastics, which can affect human health and the environment. This study aims to determine the abundance and characteristics of microplastics in local brands of bottled drinking water (AMDK) circulating in the Faculty of Public Health, Muslim University of Indonesia (FKM UMI), Makassar City. This study is an observational, descriptive study. A sample examination was conducted through laboratory analysis to identify the presence, number, shape, color, and size of microplastics in local-brand bottled water samples. The results showed that all bottled water samples examined contained microplastic particles with an average abundance of 0.028 particles/mL. The highest abundance was observed in bottled water sample 4, with 9 particles (0.038 particles/mL), while the lowest was observed in bottled water sample 2, with 4 particles (0.018 particles/mL). All identified microplastics were in fiber form. The most dominant microplastic colors were blue and black, while a small portion was transparent. The microplastics found ranged in size from 0.087 mm to 1.212 mm, with the majority measuring less than 1 mm. This study concluded that all local brand bottled water samples examined were contaminated with microplastics, with the dominant characteristics being blue and black fibers and measuring less than 1 mm. These findings highlight the need to monitor bottled water quality and further research the potential impacts of microplastics on public health.